Nutritional composition, heavy metal content and in vitro effect on the human gut microbiota of Talitrus saltator, an underutilized crustacean from the Atlantic coast - Lopez-Santamarina, Aroa; Cardelle-Cobas, Alejandra; Lamas, Alexandre; Mondragon-Portocarrero, Alicia; Cepeda, Alberto; Miranda, Jose Manuel (Frontiers in Nutrition, 2022)
IIn this study, an undervalued marine crustacean (Talitrus saltator) was characterized in terms of nutritional and heavy metal composition and its potential to affect human gut microbiota. Nutritional analysis of this crustacean revealed that it complies with the criteria established in European legislation to include nutritional claims in their labelling, such as "source of fiber", "low in fat", “low in sugars” and "high in protein". The analysis of the heavy metal content did not reveal any risk derived from the presence of Cd, Hg or Pb, whereas essential metals contained in 100 g exceeded the minimum daily requirements recommended in Europe for Zn (19.78 mg/kg), Cu (2.28 mg/kg) and Fe (32.96 mg/kg). Using an in vitro system, the effect of T. saltator on the human colonic microbiota show some beneficial effects, such as fermentation-maintained populations of Bifidobacterium or Lactobacillus, did not increase Firmicutes phylum counts, decreased the Firmicutes/Bacteroidetes ratio, and stimulated 11 metabolic pathways with respect to baseline. These results are unusual in a high protein content-food. However, negative effects were also found in gut microbiota relative proportions, such as an increase in the Proteobacteria phylum and especially some opportunistic bacteria from this phylum, probably due to the antimicrobial effect of chitin on other groups more sensitive to its effect. This work shows for the first time the effect of T. saltator on colonic microbiota using and in vitro system. The presence of chitin in its composition could provide some beneficial effects by modulating the microbiota, but as T. saltator is a a high-protein food, more studies should be carried out showing these benefits.